What has driven Chinese monetary policy since 1990? Investigating the people's bank's policy rules - Richard C. K. Burdekin; Pierre L. Siklos (Claremont McKenna College, Department of Economics, 2005)
Post-1990 Chinese monetary policy is modeled with a McCallum-type rule that takes into account the People's Bank of China's emphasis on targeting the rate of money supply growth. People's Bank policy appears responsive to the gap between target and actual nominal GDP as well as to external pressures. Additional cointegration analysis yields estimates of the gap between estimated money demand and actual money supply that appear to track the inflationary trends evident over our sample period. Chinese inflation and monetary policy outcomes seem reasonably captured using a standard monetary approach, therefore, without the need to appeal to China-specific structural factors.
Keywords: 330